Functional involvement of γ-secretase in signaling of the triggering receptor expressed on myeloid cells-2 (TREM2). Issue 1 (December 2016) - Glebov, Konstantin; Wunderlich, Patrick; Karaca, Ilker; Walter, Jochen
Abstract Background Triggering receptor expressed on myeloid cells-2 (TREM2) exerts important functions in the regulation of monocytes, like dendritic cells, osteoclasts, tissue macrophages, and microglia. Mutations in TREM2 are associated with several diseases, including Nasu-Hakola disease, frontotemporal dementia, and Alzheimer's disease (AD). TREM2 undergoes sequential proteolytic processing by ectodomain shedding and intramembrane proteolysis. Findings We show that inhibition of γ-secretase-dependent cleavage of the TREM2 C-terminal fragment in cellular membranes interferes with TREM2-dependent signaling and cellular function. Inhibition of γ-secretase decreases membrane-proximal signaling and intracellular Ca2+ response. Decreased signaling alters morphological changes and phagocytic activity of cells upon selective stimulation of TREM2. Conclusions The data demonstrate the importance of γ-secretase-dependent intramembrane processing in TREM2-mediated signaling and, thus, a functional relation of two AD-associated proteins.